The effectiveness of student-run organizations within global health promotion initiatives. (September 2015) - Byron, Yoni; West, Henry; Wood, Benjamin; Murray, Linda; Cooling, Nick
Introduction: This commentary describes a student-led project that distributed long-lasting insecticide-treated nets in Masaka, Uganda. The role of student-led initiatives in global health promotion projects is also discussed. Methods: A survey of 213 net recipients was conducted after a 12-month period to evaluate malaria prevention knowledge, and net use and maintenance. Results: Only 4.7% of recipients could not recall any malaria prevention methods. Seventy percent of pregnant women and 86.5% of children under five slept under a net the previous night. Only two households (0.9%) no longer possessed a net, and nets were not used in 2.3% of houses. Household observation revealed 17.4% of nets had at least one problem that would compromise effectiveness. Conclusions: Student-led projects can play an important role in effectively preventing malaria. However coordination with existing programs, targeting hard-to-access groups, and training of students overcomes some common limitations of such student-led initiatives.